2006
DOI: 10.1080/09712119.2006.9706572
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Analysis of Dairy Farms in the Province of Izmir (Turkey): Data Envelopment Analysis (DEA)

Abstract: Candemir, M. and Koyubenbe, N. 2006. Effkiency analysis of dairy farms in the province of Izmir (Turkey): data envelopment analysis (DEA). J. Appl. h i m. Res., 29: 61-64. The production efficiency of dairy farms based on cross section data of 2003 covering 80 farms chosen by the method of proportional sampling, was determined by Data Envelopment Analysis (DEA) using three outputs and seven inputs. Fortynine percent of the dairy farms appeared to be fully efficient according to the assumption of constant retur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 4 publications
2
7
0
Order By: Relevance
“…The percentage of farms with a score of unity (fully efficient farms) was 37% (55 farms). This is consistent with the 35% of fully efficient farms reported for Turkey and Australia (Fraser and Cordina 1999;Candemir and Koyubenbe 2006). This share is in between the 24% of fully efficient farms reported for Austria ) and the 52% reported for Argentina (Arzubi and Berbel 2001).…”
Section: Dea Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…The percentage of farms with a score of unity (fully efficient farms) was 37% (55 farms). This is consistent with the 35% of fully efficient farms reported for Turkey and Australia (Fraser and Cordina 1999;Candemir and Koyubenbe 2006). This share is in between the 24% of fully efficient farms reported for Austria ) and the 52% reported for Argentina (Arzubi and Berbel 2001).…”
Section: Dea Resultssupporting
confidence: 78%
“…Our finding indicates that 60% to 73% of the farms are inefficient when using these inputs. This is in agreement with previous studies, which reported percentages of fully efficient farms between 24% and 37% (Fraser and Cordina 1999;Candemir and Koyubenbe 2006;Kirner et al 2007;Carter Leal et al 2016). However, these studies analyzed technical efficiency as a whole, not for each input individually, as done in this study.…”
Section: Second Stage: Truncated Bootstrap Regressionsupporting
confidence: 83%
“…Similar studies have been developed in other geographical areas, as Estonia (Luik et al, 2011); Turkey (Candemir and Koyubeube, 2006; Parlakay et al, 2015; Parlakay et al; 2017; Bozoglu et al, 2017; Terin et al, 2017); Argentina (Arzubi and Berbel, 2001; 2002; Angon et al, 2013); New Zealand (Jaforullah and Whiteman, 1999); Australia (Fraser and Cordina, 1999); Canada (Weersink et al, 1990; Cloutier and Rowley, 1993); Spain (Gonzalez et al, 1996); Pakistan (Mehmood et al, 2018); and Brazil(Ferrazza et al, 2017). These studies used from 21(Arzubi and Berbel, 2002) to 264 (Jaforullah and Whiteman, 1999) dairy farms, and the majority an inputoutput oriented model from a combination of two(Luik et al, 2014) or three(Candemir and Koyubeube, 2006) outputs and to six(Luik et al, 2014) or seven(Candemir and Koyubeube, 2006) inputs, with DEA as the most used technique. However, we ought to realize that some factors constrain the efficiency scores, 728/734…”
mentioning
confidence: 99%
“…al. [19], Candemir and Koyubenbe [20], Candemir and Deliktaş [21]. This paper has five sections include part.…”
Section: Introductionmentioning
confidence: 99%